Resurrection, time, and justification: referencing Karl Barth, Wolfhart Pannenberg, and Robert Jenson - Lee, Sang Hoon ca. 21. Jh. (Lexington Books, 2023)
"This book examines the mysteries of time from the perspective of Christian theology, challenging traditional ideas and exploring the doctrines of the resurrection, justification, and retroactivity. This insightful exploration offers readers a richer understanding of the intricate relationship between time and Christian theology"--